2017
DOI: 10.1007/s00705-017-3392-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and phylogenetic analysis of three feline calicivirus strains from domestic cats in Jilin Province, China

Abstract: Feline calicivirus (FCV) is a highly prevalent pathogen that can cause infectious felid upper respiratory tract disease. The majority of complete genome sequences of FCV strains reported to date are from the USA. In this study, three FCV strains, CH-JL1, CH-JL2 and CH-JL3, were isolated from domestic cats in Jilin Province, China. Sequence analysis revealed that except for strains HRB-SS, WZ-1, XH, 12Q087-1 and 12Q087-5, the 3' untranslated regions (UTRs) of CH-JL2 and CH-JL3 are more than 20 nucleotides longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…As previously described, we determined the viral titre and relative viral RNA levels of the different strains after copper chloride treatment. The results showed that 80 μM copper chloride used to treat the other strains of FCV (CH-JL1, CH-JL3, CH-JL4, and CH-SH) isolated in ourlaboratory before [20] significantly reduced the viral titre and relative viral RNA levels of the infected F81 cells ( Fig. 5A and B).…”
Section: Antiviral Effect Of Copper Chloride On Different Strainsmentioning
confidence: 85%
See 1 more Smart Citation
“…As previously described, we determined the viral titre and relative viral RNA levels of the different strains after copper chloride treatment. The results showed that 80 μM copper chloride used to treat the other strains of FCV (CH-JL1, CH-JL3, CH-JL4, and CH-SH) isolated in ourlaboratory before [20] significantly reduced the viral titre and relative viral RNA levels of the infected F81 cells ( Fig. 5A and B).…”
Section: Antiviral Effect Of Copper Chloride On Different Strainsmentioning
confidence: 85%
“…The FCV CH-SH strains and F81 cells were provided by the Institute of Military Veterinary Medicine, Academy of Military Medical Science. FCV CH-JL1/CH-JL2/CH-JL3/CH-JL4 were isolated and stored in our laboratory [20]. The horse anti-FCV immunoglobulin F(ab') 2 was produced and stored in our laboratory [30].…”
Section: Viruses Cells and Compoundsmentioning
confidence: 99%
“…Feline kidney fibroblast-like monolayer cells (F81) and the CH-SH strain of FCV were provided by The Institute of Military Veterinary Medicine (Changchun, China). CH-JL1, CH-JL2, CH-JL3 and CH-JL4 strains of FCV were isolated and stored in our laboratory (Wang et al, 2017;Zhao et al, 2017). MZR (#M129842) and NTZ (#N159057) were purchased from Aladdin, China.…”
Section: Cells Virus Strains and Compoundsmentioning
confidence: 99%
“…The FCV CH-SH strains and F81 cells were provided by the Institute of Military Veterinary Medicine, Academy of Military Medical Science. FCV CH-JL1/CH-JL2/CH-JL3/CH-JL4 were isolated and stored in our laboratory [38]. The horse anti-FCV immunoglobulin F(ab') 2 was produced and stored in our laboratory [39].…”
Section: Viruses Cells and Compoundsmentioning
confidence: 99%